The effects of fermentation on the bioactive compounds and antioxidant activity in cruciferous vegetables - Erica, Jerica Grey Fermin (Animo Repository, 2024)
Cruciferous vegetables have been widely recognized for their abundance in bioactive compounds that contribute to their vast pharmacological benefits. Fermentation, a traditional preservation technique, imparts various changes in these bioactive compounds. Glucosinolates (GSLs) and their hydrolysis products, isothiocyanates (ITCs), as well as antioxidant activity in Malabar spinach (Basella rubra), cabbage (Brassica oleracea var capitata), mustard (Brassica juncea), radish (Raphanus sativus var longipinnatus), and Napa cabbage (Brassica rapa subsp. pekinensis) have been investigated to elucidate the effects of a 14-day fermentation period. GSL and ITC levels were quantified through HPLC analysis while antioxidant activity was investigated through a DPPH assay. Results showed that all raw extracts had much higher GSL levels with concentrations ranging from 19.55 to 384.07 umol/g while fermented samples obtained GSL levels ranging from 6.90 to 49.16 umol/g. Furthermore, hydrolysis induced an increase in ITC levels for both raw and fermented samples. Upon investigation of the hydrolyzed samples, only 5.33% to 22.78% ITC contents were retained in fermented samples except for radish which exhibited a 44.57% increase. Lastly, all vegetables obtained IC50 values ranging from 547.77 ppm to 1028.25 ppm, indicating low antioxidant activity. Additionally, fermentation changed antioxidant activity by 25.24% to 119.52%. Overall, the findings of this study suggest that fermentation elicits possible effects of degradation which lowers bioactive compounds and antioxidant activity in cruciferous vegetables. Controlled and monitored conditions play crucial roles in the fermentation process. Keywords: glucosinolates, isothiocyanates, fermentation, cruciferous vegetables, antioxidant activity